Is neighbourhood access to tobacco outlets related to smoking behaviour and tobacco-related health outcomes and hospital admissions? - Barnes, R.; Foster, S.; Pereira, Gavin; Villanueva, K.; Wood, L. (Elsevier BV, 2016)
© 2016 Elsevier Inc. Objectives: Although the harms of tobacco use are widely accepted, few studies have examined the relationship between access to tobacco outlets and hospital admissions. This study aimed to examine the relationship between neighbourhood access to tobacco outlets, smoking and hospital admissions and self-reported morbidity. Methods: Responses as to smoking behaviour were obtained from 12,270 adult participants in Western Australia (2003-2009) and individually record-linked to hospital admissions and geographically linked to tobacco outlets. Results: Neighbourhood access to tobacco outlets was marginally positively associated with being a current versus a past smoker. Tobacco outlet access was also positively associated with heart disease for smokers but not non-smokers. For smokers, each additional outlet within 1600 m of home was associated with a 2% increase in the odds of heart disease. Conclusion: Smokers with greater access to tobacco outlets were more likely to be diagnosed with or admitted to hospital for heart disease. Regulating the density of tobacco outlets in the community has immense potential to improve health benefits and our results motivate the need for future longitudinal studies to confirm this hypothesis.